Genetic analysis of PALB2 gene WD40 domain in canine mammary tumour patients - Cildir, Ozge Sebnem; Ozmen, Ozge; Kul, Selim; Risvanli, Ali; Ozalp, Gozde; Sabuncu, Ahmet; Kul, Oguz (Wiley, 2024)
Background: DNA repair mechanisms are essential for tumorigenesis and disruption of HR mechanism is an important predisposing factor of human breast cancers (BC). PALB2 is an important part of the HR. There are similarities between canine mammary tumours (CMT) and BCs. As its human counterpart, PALB2 mutations could be a predisposing factor of CMT. Objectives: In this study, we aimed to investigate the impacts of PALB2 variants on tumorigenesis and canine mammary tumor (CMT) malignancy. Methods: We performed Sanger sequencing to detect germline mutations in the WD40 domain of the canine PALB2 gene in CMT patients. We conducted in silico analysis to investigate the variants, and compared the germline PALB2 mutations in humans that cause breast cancer (BC) with the variants detected in dogs with CMT. Results: We identified an intronic (c.3096+8C>G) variant, two exonic (p.A1050V and p.R1354R) variants, and a 3 ' UTR variant (c.4071T>C). Of these, p.R1354R and c.4071T>C novel variants were identified for the first time in this study. We found that the p.A1050V mutation had a significant effect. However, we could not determine sufficient similarity due to the differences in nucleotide/amino acid sequences between two species. Nonetheless, possible variants of human sequences in the exact location as their dog counterparts are associated with several cancer types, implying that the variants could be crucial for tumorigenesis in dogs. Our results did not show any effect of the variants on tumor malignancy. Conclusions: The current project is the first study investigating the relationship between the PALB2 gene WD40 domain and CMTs. Our findings will contribute to a better understanding of the pathogenic mechanism of the PALB2 gene in CMTs. In humans, variant positions in canines have been linked to cancer-related phenotypes such as familial BC, endometrial tumor, and hereditary cancer predisposition syndrome. The results of bioinformatics analyses should be investigated through functional tests or case-control studies.
Keywords: canine mammary tumour; partner and localizer of BRCA2; PALB2; WD40 domain